Inflammatory pseudotumor of the skin mimicking non-melanoma skin cancer - Nautiyal, Hemant Kumar; Pathak, Priyank; Shirazi, Nadia; Nautiyal, Ruchira; Sachan, Praveendra Kumar (International Surgery Journal, 2017)
Inflammatory pseudo tumor (IPT) also known as inflammatory myofibroblastic tumor (IMT) or plasma cell granuloma (PCG) is mostly reported in viscera, with very rare primary cutaneous involvement. Its clinical presentation mimics non-melanoma skin cancers. This neoplasm, though considered benign, actually has intermediate biologic potential. We report a case of 52-year-old female who presented with a nodular lesion with central scab on face and hard sub mental lymph node. As patient refused for biopsy, FNAC was done, which showed highly atypical cells suggestive of squamous cell carcinoma from nodular lesion and reactive hyperplasia from lymph node. Patient underwent excision biopsy and supra-omohyoid lymph node dissection. Biopsy report showed it as inflammatory pseudo tumor of the skin and cervical lymph nodes showed non-caseating granuloma. We present review of this entity.